Application of Cultural–Historical Analysis in Child Clinical Psychology - Burlakova, N; Oleshkevich, V (KnE Life Sciences, 2018)
The article presents summarized results of qualitative studies exploring child development in norm and pathology; studies were conducted within the framework of cultural–historical approach developed by L.S. Vygotsky and A.R. Luria and aimed at further methodological elaboration of the approach. The article demonstrates that such research needs to be multidimensional and to include multilevel analysis; it stresses on the importance of analyzing developmental norms in the context of certain social groups, subcultures, etc. The article explores shaping of developmental risks in certain cultural settings and insists on the significance of understanding developmental deviations in the context of normative developmental matrix approved by this social group. The conducted study demonstrates how this method of assessment allows to evaluate structural peculiarities and inner psychodynamics of developmental deviations more precisely within the reconstructed developmental matrix. Such data structure describing child development in certain social group allows to organize correction of development in a systematic manner as well as to design optimal organization of development. Keywords: cultural–historical analysis, psychological development, developmental norms, child clinical psychology